Does brain entrainment using binaural auditory beats affect pain perception in acute and chronic pain?: a systematic review - Fatemeh Shamsi; Fatemeh Azadinia; Maryam Shaygan (BMC, 2024)
Abstract Background Pain is a major clinical problem across all ages with serious social and economic consequences and a great negative impact on quality of life. Brain entrainment using binaural beats is a non-pharmaceutical intervention that is claimed to have analgesic effects in acute and chronic pain. We aimed to systematically review the available randomized clinical trials on the efficacy of binaural auditory beats in reducing adults' pain perception in acute and chronic pain. A systematic search in electronic databases including Medline (via PubMed), Web of Science, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), and Embase was performed. The search was completed through Google Scholar and a manual search of the reference lists of all included studies. Randomized clinical trials with full text available in English that investigated the effect of binaural auditory beats on pain perception in acute and chronic pain in adults were included. The risk of bias was assessed by the revised Cochrane risk-of-bias (RoB 2) tool. Furthermore, The GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach was used to assess the quality of the evidence. Sixteen studies (three on chronic pain and thirteen on acute pain perception) fulfilled the eligibility criteria. Because of substantial heterogeneity of the studies, a meta-analysis was inappropriate and this review focused on the narrative interpretation of the results. The risk of bias in most studies was high and the quality of evidence was low to very low. Although the effects of binaural beats on pain perception seem to be influenced by the etiology of pain or medical procedures, our review identifies alpha or a combination of tones in the range of delta to alpha as a potential non-pharmacological intervention in reducing acute pain. However, drawing a conclusion regarding the efficacy of binaural beats for chronic pain requires more high-quality studies. Registration The protocol of this review was registered in PROSPERO (No. CRD42023425091).